Non‐motor symptoms burden in treated and untreated early Parkinson's disease patients: argument for non‐motor subtypes. (15th May 2015) - Zis, P.; Martinez‐Martin, P.; Sauerbier, A.; Rizos, A.; Sharma, J. C.; Worth, P. F.; Sophia, R.; Silverdale, M.; Chaudhuri, K. Ray
<x xml:space="preserve">Abstract</x> Background and purpose Non‐motor symptoms (NMSs) occurring at an early stage of Parkinson's disease (PD) may impair quality of life more than motor symptoms. This study aimed to evaluate the severity of overall NMS profile and burden of NMSs in early PD patients, treated (time since confirmed diagnosis of 5 years or less) or drug naive (DN). Methods Cross‐sectional data from an ongoing multicentre study (16 sites) were obtained and specifically an NMS data set from validated scales was analysed in treated and DN PD patients. Results A full data set was available in 234 unique early PD patients. Of them, there were 170 treated (63.5% males, mean age 68.2 years) and 64DN patients (64.1% males, mean age 66.5 years). Compared to DN patients the time since confirmed diagnosis was significantly longer in treated PD patients (1.9 years vs. 3.7 years, P < 0.001). Fatigue (57.7%), urinary urgency (57.1%), nocturia (55.3%), memory difficulties (51.2%) and urinary frequency (48.8%) were the most prevalent NMSs amongst treated PD, whereas DN PD reported most frequently sadness (57.8%), fatigue (57.8%), lightheadedness (53.1%), memory difficulties (48.4%) and urinary urgency (46.9%). Conclusions Our results suggest that NMSs are dominant in the untreated and early phase of PD causing a considerable burden. This warrants investigation of the issue of NMS subtyping within PD.